2007
DOI: 10.2320/jinstmet.71.959
|View full text |Cite
|
Sign up to set email alerts
|

A New Wire Fabrication Processing Using High Ga Content Cu-Ga Compound in V3Ga Compound Superconducting Wire

Abstract: A superconducting magnet system is also one of the important components in an advanced magnetic confinement fusion reactor. Then it is required to have a higher magnetic field property to confine and maintain the steady state burning deuterium (D) tritium (T) fusion plasma in the large interspace during the long term operation. Burning plasma is sure to generate 14 MeV fusion neutrons during deuterium tritium reaction, and fusion neutrons will be streamed and penetrated to superconducting magnet through lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…thought that the high Ga content in the Cu-Ga compound material was an effective method to improve J C of the V 3 Ga compound wire, just like the high Sn content Nb 3 Sn wires. They tried to develop the new route for the fabrication of V 3 Ga compound wire with high Ga content Cu-Ga compound using the PIT processed precursors in order to improve the cold workability and volume fraction of the synthesized A15 phase, and investigated its microstructure and superconducting properties [3,4]. It was confirmed that the thicker V 3 Ga layer formed along the interface of Cu-Ga powder core and V matrix compared with previous diffusion processed samples for the multifilamentary wires.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…thought that the high Ga content in the Cu-Ga compound material was an effective method to improve J C of the V 3 Ga compound wire, just like the high Sn content Nb 3 Sn wires. They tried to develop the new route for the fabrication of V 3 Ga compound wire with high Ga content Cu-Ga compound using the PIT processed precursors in order to improve the cold workability and volume fraction of the synthesized A15 phase, and investigated its microstructure and superconducting properties [3,4]. It was confirmed that the thicker V 3 Ga layer formed along the interface of Cu-Ga powder core and V matrix compared with previous diffusion processed samples for the multifilamentary wires.…”
Section: Introductionmentioning
confidence: 96%
“…It is also one of the important components in an advanced magnetic confinement fusion reactor [1]. In previous study, V 3 Ga compound wire was mainly investigated the "Diffusion process" between Cu-Ga solid solution matrix within 20 at% Ga composition and V filament [2]. It has been reported that the drastic critical current density (J C ) of Nb 3 Sn will be improved by increasing Sn content in the Cu-Sn matrix.…”
Section: Introductionmentioning
confidence: 99%
“…It is also one of the important components in an advanced magnetic confinement fusion reactor [1]. In previous study, V 3 Ga compound wire was mainly investigated "Diffusion process" between Cu-Ga solid solution matrix within 20 at% Ga composition and V filament. The drastic critical current density (J C ) improvement by increasing of Sn content in the Cu-Sn matrix on Nb 3 Sn was reported.…”
Section: Introductionmentioning
confidence: 99%
“…thought that the high Ga content in the Cu-Ga compound material was an effective method in order to improve J C of the V 3 Ga compound wire, just like for the high Sn content processed Nb 3 Sn wires. They tried to develop the new route wire fabrication of V 3 Ga compound wire using high Ga content Cu-Ga compound through the PIT processed precursors in order to improve cold workability and volume fraction of synthesized A15 phase, and investigated its microstructure and superconducting properties [2,3]. It was confirmed that the thicker V 3 Ga layer formed along the interface of Cu-Ga powder core and V matrix compared with previous diffusion processed samples in the case of the multifilamentary wires.…”
Section: Introductionmentioning
confidence: 99%